Bahasa Tolaki di Kalangan Anak Remaja dalam Kehidupan sehari-hari di Desa Totombe Jaya - Indriyani Indriyani; Sarlan Adi Jaya (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This study aims to determine the influence and causes of the Fading of the Use of Tolaki Language Among Adolescent Children in Sampara District in Konawe Regency. The selection of informants in this study used purposive techniques. This research uses Bronislaw Malinowski's Cultural Diffusion theory (1944) The data collection technique used in this research is a field work technique using observation and in-depth interviews. This research is qualitative research with ethnographic research methods. The results of this study show that: First, several things make teenagers there cannot speak Tolaki, namely because of several external and internal factors. The internal factor is the family. While external factors are school and friends. Second, due to habits from childhood, they are not taught from childhood, making it difficult for them to know their local language. This makes the teenagers there no longer use Tolaki regional language anymore but to the general language of Indonesian.